DEVELOPING NEW PRODUCT USING MINIMUM VIABLE PRODUCT - Aghnia, Mutiara Cahya; Larso, Dwi (Universitas Brawijaya, Indonesia, 2018)
The goal of this research is to make a new product, get a result of the sales, get feedback on the new product, and look at the product acceptability. The methodology used is a qualitative method. The research was done as a field research which developing a new product and tests it to the market using Minimum Viable Productfrom Lean Startup. Customer interview shows that customers need moreitabag colors. From internal and external analysis using SWOT show, there is a strength in Colle customer service and an opportunity for new fabric printing technology. The MVP is a catalog, published online and tested for 2 weeks and get 11 purchases as the result. After the test period, 5 customers were interviewed, they need a wider choice of color, pattern, illustration, and want their own images for itabag. This result then implemented on MVP improvement. This research will only include the first test due to the time limitation. If possible, for the future researcher, more test of the product will be better.